Adult ADHD: Questioning Diagnosis and Treatment in a Patient with Multiple Psychiatric Comorbidities. (11th June 2017) - Chu, Robert Karoly; Rosic, Tea; Samaan, Zainab
Abstract : Adult Attention-Deficit/Hyperactivity Disorder (ADHD) is a contentious diagnostic issue, which has been increasing in prevalence in recent years, and is often comorbid with other psychiatric disorders. This report presents a detailed account of a clinical case involving a middle-aged man with a history of recurrent depressive episodes and an unsubstantiated diagnosis of ADHD, treated with stimulants. There is persistent debate around the use of psychostimulants both in adult ADHD and in the treatment of depression. Despite promising activating properties, psychostimulants carry significant risks of misuse and substance use disorder. In this report, we consider the potential benefits and adverse effects of stimulants in the treatment of adult ADHD and mood disorders and review the learning points of this complicated, but not uncommon, clinical case.